Can we forecast the effects of climate change on entomophagous biological control agents? - Aguilar-Fenollosa, Ernestina; Jaques, Josep A. (2017)
The worldwide climate has been changing rapidly over the past decades. Air temperatures have been increasing in most regions and will probably continue to rise for most of the present century, regardless of any mitigation policy put in place. Although increased herbivory from enhanced biomass production and changes in plant quality are generally accepted as a consequence of global warming, the eventual status of any pest species will mostly depend on the relative effects of climate change on its own versus its natural enemies' complex. Because a bottom-up amplification effect often occurs in trophic webs subjected to any kind of disturbance, natural enemies are expected to suffer the effects of climate change to a greater extent than their phytophagous hosts/preys. A deeper understanding of the genotypic diversity of the populations of natural enemies and their target pests will allow an informed reaction to climate change. New strategies for the selection of exotic natural enemies and their release and establishment will have to be adopted. Conservation biological control will probably become the keystone for the successful management of these biological control agents. (c) 2013 Society of Chemical Industry